THE MYTH OF THE CHARGE AND DISCHARGE STATEMENT. - Hay, Leon E. (The Accounting Review, 1956)
Abstract The traditional form of the charge and discharge statement based on the practices of the Surrogate's Court of the County of New York has been presented in accounting texts for over fifty years. This manner of presentation has given three generations of accounting students the impression that this form is appropriate for use by executors and administrators throughout the United States. An evaluation of the form, however, indicates that it does not meet requirements common to the majority of states. A further evaluation of the form indicates that it does not pass the tests of a good accounting report either. The disposition of any other item in the inventory would be as difficult to ascertain from a charge and discharge statement as was that of the bonds. It is also apparent that in many states this form of report would be unacceptable because it does not contain a statement of the receipts and disbursements of estate cash. Even though this form of report is deficient in these respects, it does meet or exceed the requirements of most states in that it contains listings of both beginning and ending inventories of estate assets.